Murray Krieger's "Everyday Language, Literary Language, and the Problem of Translation": Roundtable Discussion - Adams, Hazard; Behler, Ernst; Birus, Hendrik; Derrida, Jacques; Iser, Wolfgang; Krieger, Murray; Miller, Hillis; Pfeiffer, Ludwig; Readings, Bill; Wang, Ching-hsien; Yu, Pauline (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1996)
This roundtable discussion of "Everyday Language, Literary Language, and the Problem of Translation", Murray Krieger's contribution to the first International Conference for Humanistic Discourses, was held in April, 1994. The papers of this first meeting of the ICHD have been published in volume 4 of Surfaces (1994).